IMPLEMENTATION OF STANDARD OPERATING PROCEDURES DISCIPLINE ON EMPLOYEES OF PT BPRS TUNAS ARTHA JAYA ABADI NGADILUWIH - Angga Wanda Aryanta; Endah Kurniawati (SOSIOEDUKASI, 2025)
This study examines the implementation of Standard Operating Procedures (SOP) on employee discipline at PT BPRS Tunas Artha Jaya Abadi Ngadiluwih, which plays a crucial role in maintaining organizational performance through the development of a disciplined work culture. The background of this research lies in the fact that although the company has applied a fingerprint attendance system and sanctions in the form of meal allowance deductions, employee discipline is still often understood merely as an administrative obligation rather than as an internalized behavior. The purpose of this study is to analyze the implementation of disciplinary SOPs, identify the challenges faced, and formulate improvement strategies to create a sustainable culture of discipline. This research employed a qualitative descriptive approach with data collected through interviews, observations, and documentation involving the branch leader and section heads as key informants. The data obtained were analyzed systematically through selection, categorization, and drawing conclusions based on emerging patterns in the field. The findings indicate that punishment in the form of meal allowance deductions has been applied consistently, yet rewards specifically for discipline have not been implemented evenly and remain focused on work target achievements. Moreover, disciplinary assessments are still limited to attendance, while other essential aspects such as procedural compliance, work ethic, and initiative have not received sufficient attention.